THE AUSTRIAN VACCINATION PARADOX: TICK-BORNE ENCEPHALITIS VACCINATION VERSUS INFLUENZA VACCINATION - Kunze, Ursula; Kunze, Michael (Central European journal of public health, 2015)
This paper describes a paradoxical situation in Austria. The vaccination rate against tick-borne encephalitis (TBE) in the general population is 82%, which is the highest worldwide, whereas the vaccination rate against influenza is about 8% and is among the lowest worldwide. A high awareness of TBE among the Austrian population achieved by an annual social marketing programme and the wide use of effective and well-tolerated vaccines have led to a successful containment of that disease. The vaccination coverage increased from 6% in 1980 to 82% in 2013 and exceeds 90% in some high-risk areas. This has led to a steady decline in the number of TBE cases from several hundred cases to 50 to 100 cases per year. The situation in regard to influenza vaccination is the opposite. Although Austria has issued one of the most extensive recommendations for influenza vaccination worldwide, the vaccination rate of the general population is extremely low. The possible reasons for the failure in the implementation of recommendations are ignorance, lack of social marketing and the predominance of a distinct discordance within the health system in general, and the Austrian medical fraternity in particular.
Keywords: chřipka lidská; pacientův souhlas se zdravotní péčí; Influenza, Human; Humans; lidé; podpora zdraví; vakcíny proti chřipce; virové vakcíny; klíšťová encefalitida; Austria; Influenza Vaccines; Social Marketing; Health Promotion; Viral Vaccines; Patient Acceptance of Health Care; Rakousko; sociální marketing; Encephalitis, Tick-Borne